Assessment of Health Beliefs Among Iraqi Breast Cancer Patients in Baghdad using either Tamoxifen or Trastuzumab - Mohammed, Samer Imad; Sabry, Aya Thaer; Sabry, Dania Thaer (Iraqi Journal of Pharmaceutical Sciences, 2021)
Breast cancer is the most diagnosed form of malignant tumour in Iraqi women. Tamoxifen and trastuzumab are highly effective adjuvant therapy for breast cancer. This study’s objectives were to define the patient’s belief in tamoxifen or trastuzumab when used as adjuvant therapy and to determine the variation in belief between the two medications in a sample of Iraqi breast cancer patients. The cross-section survey was conducted using the BMQ-Specific questionnaire. Ninety-seven participants (sixty-seven tamoxifen, thirty trastuzumab) participated in this study. The mean of specific-necessity scale for tamoxifen was (3.7) and for trastuzumab (4). The findings showed a high necessity for both medicines, and there were no significant differences in the scale of necessity between the two treatments. Regarding the scale of concern, the trastuzumab group’s values are higher (3.35) than tamoxifen (3). Most participants who use tamoxifen or trastuzumab strongly agree with or agree with all the questions on the necessity scale with higher percentages for trastuzumab. Besides, the concern scale results showed the percentage of patients who agree / strongly agree is higher in the trastuzumab group. For the correlation between the need or concern score, the result showed only one significant negative correlation (R=-0.366, P-value=0.011) between the necessity score and the age of the participants for tamoxifen users. In Conclusion, this survey clearly showed a high level of necessity and a high level of concern regarding the use of two effective adjuvant therapy for women with breast cancer, tamoxifen and trastuzumab. Furthermore, this study shows that while the level of need for tamoxifen is higher than for trastuzumab, there were no significant variations between them.